The potential of ME1 in guiding immunotherapeutic strategies for ovarian cancer: insights from pan-cancer research - Wei, Jiahui; Wang, Ming; Xu, Shuiqing; Tusufuhan, Paizigul; Wu, Yumei (Frontiers in Immunology, 2025)
ObjectiveME1 catalyzes the conversion of malic acid into acetic acid, thereby linking glucose metabolism to the citric acid cycle. In recent years, the role of ME1 in various tumors has only been superficially explored. Therefore, our objective is to analyze the potential functions of ME1 in pan-cancer, with a particular focus on its role in ovarian cancer.MethodsWe analyzed the ME1 expression levels in both normal and tumor tissues across various cancer types. CBIOPORTAL was utilized to assess the mutation frequency and specific sites of ME1. Additionally, we examined the correlation between ME1 expression and several factors, including methylation status, tumor mutation burden (TMB), microsatellite instability (MSI), immune regulator genes, immune checkpoints, tumor microenvironment scores, functional enrichment, single-cell analysis, and drug sensitivity. The Estimate Algorithm assessed the correlation between ME1 expression and the tumor immunochemical microenvironment. Small interfering RNA and chronic viruses were utilized to downregulate and upregulate ME1 expression in two ovarian cancer cell lines, respectively, to conduct experiments on cell proliferation and migration.ResultsOur results revealed that ME1 exhibited disorders across various tumors, with the predominant form of genetic mutation identified being a missense mutation. Among the various tumors analyzed, ME1 demonstrated a significant correlation with methylation levels, TMB, MSI, immune checkpoints, immunomodulatory regulatory genes, tumor microenvironment scores, and immune infiltration. Functional enrichment analysis and single-cell analysis indicated that ME1 expression was associated with metabolic regulation, macrophage immune responses, antioxidant defense mechanisms, and the potential tumor microenvironment. The elevated levels of ME1 may be associated with a more favorable response to specific immunotherapy, suggesting that ME1 has potential applications in guiding immunotherapeutic strategies. In vitro research results demonstrated that in ovarian cancer cell lines, the knockdown of ME1 inhibited the proliferation and migration of tumor cells. Conversely, the overexpression of ME1 appeared to promote tumor cell proliferation and migration.ConclusionsME1, a metabolic-related factor, has the potential to serve as a biomarker for tumor progression and immune infiltration, particularly in ovarian cancer. It may signify a metabolic reprogramming that supplies energy for tumor progression and immunotherapy, offering valuable insights for the development of personalized therapies.